Implementasi Pengelolaan Kekayaan Milik Desa Sebagaimana yang Diamanatkan dalam Pasal 77 Ayat (1) Undang-Undang Nomor 6 Tahun 2014 - Styaningsih, Rahayu Utami; Destyarini, Normalita; Aryono, Aryono; Elisanti, Evi (Fakultas Syariah INSURI Ponorogo, 2023)
The aim of this research is to determine the mechanisms and obstacles to managing village property, as mandated in Article 77 paragraph (1) of Law Number 6 of 2014. The research method used is empirical juridical. The type of data, namely primary data, was obtained through interviews and discussions (group discussion forum) with several parties to provide information related to the management of village property. Secondary data is data obtained from library literature. Data collection techniques commonly used are literature studies, interviews, observations. Qualitative descriptive data analysis techniques. The results of the research show that the mechanism for managing village property as mandated by Article 77 paragraph (1) of Law Number 6 of 2014 is planning, procurement, use, utilization, security, maintenance, deletion, transfer, administration, assessment, guidance, supervision and control. . Inventory village assets in the SIPADES application, check the depreciation in the value of goods, including land, buildings and other assets. Providing information about village asset management to the general public so that village asset management is reported annually. Obstacles to managing village-owned assets include lack of knowledge of human resources regarding village asset management, SIPADES officers being disorganized in inputting data, the community not caring about maintaining village assets, lack of communication regarding the implementation of village asset management regulations. The conclusion of this research is that the village's wealth management mechanism is to inventory its assets in the SIPADES application and can reduce problems.